Correction: Corrigendum: The OncoPPi network of cancer-focused protein–protein interactions to inform biological insights and therapeutic strategies - Zenggang Li (Nature Portfolio, 2017)
Nature Communications 8: Article number: 14356 (2017); Published: 16 February 2017; Updated: 18 April 2017 The original version of this Article contained an error in the spelling of the author Carlos S. Moreno, which was incorrectly given as Carlos Moreno. This has now been corrected in both the PDFand HTML versions of the Article.